Effect of charge transfer and structural rigidity on divergent luminescence response of a metal organic framework towards different metal ions: luminescence lifetime decay experiments and DFT calculations. Issue 5 (12th February 2019) - Majee, Prakash; Singha, Debal Kanti; Mondal, Sudip Kumar; Mahata, Partha
Abstract : A Cd based MOF showing both luminescence turn-on and quenching behavior in presence of different metal ions. Abstract : We have thoroughly studied the luminescence behaviour of a cadmium based MOF, [Cd(C12 N2 H8 )(C7 N1 O4 H3 )] C12 N2 H8 = 1, 10-phenanthroline, C7 N1 O4 H3 = 2, 5-pyridine dicarboxylate, 1 . Both steady-state and time-resolved luminescence spectroscopic experiments were performed to understand the dissimilar responses of compound1 towards different metal ions in aqueous medium. Upon excitation at 280 nm, compound1 showed a luminescence spectrum centered at 365 nm, which exhibited a three-fold turn-on in the presence of a trace amount of Zn 2+ in aqueous solution, whereas in the presence of Co 2+, Hg 2+, Ni 2+, Fe 2+ and Cu 2+ the luminescence of compound1 got largely quenched. Compound1 did not show any response in the presence of other common metal ions such as K +, Mg 2+, Na +, Mn 2+, and Cr 3+ . By analysing all the experimental results, we successfully explained the versatile luminescence behaviour of compound1 . The turn-on of luminescence in the presence of Zn 2+ ions was due to coordination bond formation and enhancement of the rigidity of compound1 which resulted in the reduction of non-radiative decay processes to a large extent. The quenching of luminescence in the presence of transition metal ions was found to be static in nature, and was due to the possibility of ligand to metal charge transfer using the vacant d-orbital of the metal ions. In the case of Hg 2+ which is a closed cell heavy metal ion, the quenching of luminescence was also static in nature and was due to a two-way charge transfer mechanism. We have also performed density functional theory calculations and obtained supportive results for the proposed mechanisms of luminescence turn-on and quenching. Moreover, compound1 could be established as a selective and efficient sensor of Zn 2+ in aqueous solution even in the presence of Cd 2+ and other metal ions.